Fungi Associated With Chickpea, Lentil And Blackgram Seeds of Rajasthan - TRIPTI AGARWAL,; ABHINITI MALHOTRA,; P. C. TRIVEDI, (International Journal of Pharma and Bio Sciences, 2011)
The study aims at identifying pathogenic fungi associated with chickpea (Cicer arietinum L.), lentil(Lens culinaris) and black gram(Vigna mungo (L.) seeds. Seed health testing is a pre requisite for seed improvement, seed production, seed certification and trade in seed. Direct analysis of seed has been a much more effective means of identifying infected seed lots than the field inspection required for phytosanitary certification. Samples of chickpea, lentil and black gram seeds are collected from local districts of Rajasthan and are analyzed for seed-borne fungi. The fungi isolated from these seeds are Alternaria alternata, Chaetomium spp., Penicillium citrinum, Aspergillus niger, A. flavus, Rhizopus nigricans,Fusarium oxysporum.